T. C. Chao's thoughts on "Sinicization of Christianity" - ZHANG, Zhigang (Journal of Research for Christianity in China (JRCC), 2025)
T. C. Chao (1888-1979), a famous Chinese Christian philosopher, theologian, educator, and literary scholar, is a pioneer in advocating the "Sinicization of Christianity. Although scholars at home and abroad have long paid attention to the thought of "Sinicization of Christianity" expounded by T. C. Chao, it has not been systematically studied. In this paper, we try to deepen one layer on the basis of previous researches, that is, to focus on the problematic consciousness of T. C. Chao's thought of "Sinicization of Christianity", to investigate the logical progression of his thought, and to discover the significance of his thought in the times.
Keywords: Western Christianity, Authentic Christianity, Chinese culture, Chinese nation, Sinicization of Christianity